Evolução histórico-cultural e paisagística da Praça Dr. José Esteves e entorno em Lavras - MG - Luz, Iracema Clara Alves (2015)
The origin and transformation studies of one square throughout the time is extremely important, resulting in preservation of the local identity and regional culture, creating a patrimonial awareness in intention to promote its history conservation. Many of these gardens are present in many localities and in particularly in the Minas Gerais colonial cities that has roots in the unceasing search for gold and in the planned routes of the Royal Road (Estrada Real). In this purpose the aim of this study was to building the historic-cultural and landscape evaluation of the Dr. José Esteves Square and its surroundings, located in Lavras - MG, Brazil, a city established by pioneers and on the Royal Road old route. This research focused on the period between 1721 (Lavras city foundation year) and 2014, whereas the field research was set from August, 2013 to July, 2014. The data collected was taken from this field research with visits and talks previously scheduled, in addition to documental, bibliographic and photographic research. The Dr. José Esteves Square was created in order to ornament and give a support to the passengers arrivals in the train station turning into this scenery in an important political, military and cultural space. Its emergence occurred in a different way from many Brazilian’s squares, which normally had their construction related to churches. Since its construction until nowadays, the square recieved minimal changes in its layout, however its vegetation was drastically modified. The lack of maintenance of this space in addition to the privatization and the abandonment of the train station in the end of 1990's, besides of the fact that its surroundings had not accompanied the economic development of the municipality, result in the gardens and surrounds loss of the importance and aesthetical features that present in the past.